Kansas Field Research 2022 (Kansas Agricultural Experiment Station Research Reports, 2022)
A summary of research conducted in 2020-2022 on field production and management practices for crops in Kansas. Published in 2022 from the Kansas State University Agricultural Experiment Station and Cooperative Extension Service. https://www.ag.k-state.edu/
Keywords: corn; tillage; sorghum; management practices; soybean; Kansas weather; weed science; wheat; planting dates; grain weight; tiller yield; vertical tillage; no-till; deep till; grazing; cover crops; soil properties; soil evaporation; residue cover; nitrogen management; forage accumulation; dryland; irrigation; fungicide management; seeding rate; seed cleaning